Places of memory : the case of the house of the Wannsee Conference - Digan, Katie (Palgrave Pivot, 2015)
In 1942, a group of high-ranking Nazis came together in a villa in Berlin to discuss the Final Solution, during what is now called the Wannsee Conference. Fifty years later that same villa was turned into a memorial site and museum for one of the most infamous episodes of the history of the Holocaust. Today, hundreds of people a day visit the house to learn about its history. Why did it take so long for the house to become a 'site of memory'? And what happened to the house in the meantime? This book takes the case of the House of the Wannsee Conference as a starting point to investigate how and why buildings and places transform from regular places to 'carriers of memory'. How can a house become haunted by its past? And why do we visit historical places to get a sense of the past?